Răspunsuri

2014-08-18T22:55:10+03:00


1) 3^x[1 + 3+ 3^2 + 3^3+3^4 ]=(3²)²×11²  împărțim expresia la 3^ 4     ⇒                             3^(x-4) ×[1+3+3^2+3^3+3^ 4] =11²

S=1+3+3² +3³ +3^4            3S=3+3² +3³ +3^4 +3^5     3S-S=2S= 3^5 -1 ⇒ S=(3^5 -1)/2 ⇒3^(x-4)×121=11² ⇒3^(x-4)=1⇒x-4=0 ⇒x=4

2) 3^6(x+3) +3^6(x+3) + 3^6(x+3) =3^{4(x+6)+237}

3[ 3^(x+3)]=3^{4(x+6)+237}     3^(x+4)=3^{4(x+6)+237}⇒ x+4= 4(x+6)+237 ⇒x+4=4x+24+237⇒x+4=4x+261 ⇒3x= - 257 ....undeva s-a strecurat o greseala (in enunt, sau in rezolvare)  verificati si corectati